A gap-filling, regenerative implant for open-wedge osteotomy - Margot Rikkers; H. Chien Nguyen; Nasim Golafshan; Mylène de Ruijter; Riccardo Levato; Lucienne A. Vonk; Nienke van Egmond; Miguel Castilho; Roel J.H. Custers; Jos Malda (Elsevier, 2023)
Introduction: In patients suffering from unilateral osteoarthritis in the knee, an osteotomy can provide symptomatic relief and postpone the need for replacement of the joint. Nevertheless, open-wedge osteotomies (OWOs) around the knee joint face several challenges like postoperative pain and bone nonunion. Objectives: In this study, the aim was to design, fabricate, and evaluate a gap-filling implant for OWO using an osteoinductive and degradable biomaterial. Methods: Design of porous wedge-shaped implants was based on computed tomography scans of cadaveric legs. Implants were 3-dimensionally printed using a magnesium strontium phosphate-polycaprolactone (MgPSr-PCL) biomaterial ink. Standardized scaffolds with different inter-fiber spacing (IFS) were mechanically characterized and osteoinductive properties of the biomaterial were assessed in vitro. Finally, human-sized implants with different heights (5 mm, 10 mm, 15 mm) were designed and fabricated for ex vivo implantation during 3 OWO procedures in human cadaveric legs. Results: Implants printed with an interior of IFS-1.0 resulted in scaffolds that maintained top and bottom porosity, while the interior of the implant exhibited significant mechanical stability. Bone marrow concentrate and culture expanded mesenchymal stromal cells attached to the MgPSr-PCL material and proliferated over 21 days in culture. The production of osteogenic markers alkaline phosphatase activity, calcium, and osteocalcin was promoted in all culture conditions, independent of osteogenic induction medium. Finally, 3 OWO procedures were planned and fabricated wedges were implanted ex vivo during the procedures. A small fraction of one side of the wedges was resected to assure fit into the proximal biplanar osteotomy gap. Preplanned wedge heights were maintained after implantation as measured by micro-computed tomography. Conclusion: To conclude, personalized implants for implantation in OWOs were successfully designed and manufactured. The implant material supported osteogenesis of mesenchymal stromal cells and bone marrow concentrate in vitro and full-size implants were successfully implemented into the surgical procedure without compromising preplanned wedge height.